Building up - Elizabeth Kellogg; Kara Vander Linden (Grounded Theory Review: An International Journal, 2021)
The theory of building up, developed using classic grounded theory (CGT), explains how the fit between an individual and a transformational opportunity impacts the extent to which an individual is empowered by that experience. Classic grounded theory identifies and explains human behavior patterns using an inductive, iterative process of data collection and analysis. Theoretical sampling guided data collection and constant comparative analysis of data, which yielded building up as the core pattern of behavior in negotiating challenges through transformative opportunities. Building up summarizes the potential outcomes of participation in an opportunity based on the fit of the interaction of variables in the individual and in the opportunity. An optimal fit is ideal; however, most relevant for practical applications are the variables that most frequently contribute to a good enough fit, which are deconstructing limiting beliefs, feeling supported within the experience, a sense of agency, and the timing of the opportunity.